A CASE REPORT ON AYURVEDIC MANAGEMENT OF TYPE 2 DIABETES MELLITUS - FARSEENA K; SHAILESH DESHPANDE (The Bioscan, 2025)
Diabetes mellitus is a multifactorial metabolic disorder with increasing prevalence, contributing significantly to the global health burden. Given its impact on multiple organ systems, emphasis on prevention, early detection, and appropriate management is crucial. This case report presents a 56-year-old male patient with a 10-year history of diabetes, previously managed with allopathic medication, who sought consultation at the OPD of Government Ayurveda College Hospital, Kannur, Kerala. The patient presented with complaints of increased frequency of urination, excessive thirst, fatigue, foul-smelling sweat, oedema in the feet, and burning micturition. A comprehensive evaluation of the patient’s clinical condition, including an assessment of dosha, dooshya, and srothas, led to the administration of a Kapha-Medohara treatment protocol. This Ayurvedic intervention resulted in significant improvement in the patient’s symptoms, highlighting the potential of integrative approaches in managing chronic metabolic disorders like diabetes.